2018
DOI: 10.5194/nhess-18-1297-2018
|View full text |Cite
|
Sign up to set email alerts
|

Multi-model ensembles for assessment of flood losses and associated uncertainty

Abstract: Abstract. Flood loss modelling is a crucial part of risk assessments. However, it is subject to large uncertainty that is often neglected. Most models available in the literature are deterministic, providing only single point estimates of flood loss, and large disparities tend to exist among them. Adopting any one such model in a risk assessment context is likely to lead to inaccurate loss estimates and sub-optimal decision-making. In this paper, we propose the use of multi-model ensembles to address these iss… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 57 publications
(58 citation statements)
references
References 55 publications
0
53
0
1
Order By: Relevance
“…They have the advantage of inherently quantifying uncertainty associated with the loss estimation. Thus, a variety of models with varying complexities and working concepts are currently available, and it is not trivial to decide which one to use for a specific application (Apel et al, 2009;de Moel et al, 2015;Figueiredo et al, 2018). Several studies have tested and compared various flood loss models in respect to their predictive accuracy and reliability (e.g., Cammerer et al, 2013;Gerl et al, 2016;Hasanzadeh Nafari et al, 2016;Jongman et al, 2012).…”
Section: 1029/2018ef000994mentioning
confidence: 99%
“…They have the advantage of inherently quantifying uncertainty associated with the loss estimation. Thus, a variety of models with varying complexities and working concepts are currently available, and it is not trivial to decide which one to use for a specific application (Apel et al, 2009;de Moel et al, 2015;Figueiredo et al, 2018). Several studies have tested and compared various flood loss models in respect to their predictive accuracy and reliability (e.g., Cammerer et al, 2013;Gerl et al, 2016;Hasanzadeh Nafari et al, 2016;Jongman et al, 2012).…”
Section: 1029/2018ef000994mentioning
confidence: 99%
“…Despite the progress in damage estimation in recent years (Figueiredo et al, 2018;Kreibich et al, 2016;Schröter et al, 2014;Sieg et al, 2017;Wagenaar et al, 2017), the available damage models are not able to describe the damage process reliably, and the process is stochastic to a substantial extent. Therefore, as implemented in this approach, the distribution of the damage estimate should be assessed at every spatial scale in order to report the lack of knowledge about the damage estimates.…”
Section: The Role Of Vulnerability Uncertaintymentioning
confidence: 99%
“…to the final damage estimations. It was demonstrated that the uncertainty related to this component represents a dominant factor affecting the overall uncertainty of damage assessments (De Moel and Aerts, 2011), especially when damage calculations are applied in deterministic ways (Figueiredo et al, 2018). Additionally, damage models are generally site-dependent.…”
Section: Discussionmentioning
confidence: 99%
“…The type of flood hazard and related damage models are also important, as marine floods are different from fluvial ones in terms of consequences to buildings (e.g., salinity, short-period waves). These aspects contribute to lower the predictive skills of damage models (Figueiredo et al, 2018). The damage curve used in this study (adapted from Scorzini and Frank, 2017) was developed for residential buildings, for a fluvial flood occurred in Veneto in 2010.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation